Assessment of Serum Apelin Level in Iraqi Type 2 Diabetic Nephropathy Patients - Raheem, Raghad; Al-Qaisi, Alaa Hussein J.; Mohammed, Salam (Al-Nahrain Journal of Science, 2023)
The present study is investigated the relationship between Apelin concentration and various biochemical parameters in patients with type 2 diabetic nephropathy. A total of 30 patients diagnosed with Diabetic Nephropathy at Al-Yarmouk and Al-Karama teaching hospitals were included in the study and compared to 40 healthy individuals forming the control group. The study was identified a significant increase in Apelin concentration among patients with type 2 diabetic nephropathy, compared to the control group. Additionally, various biochemical parameters were analyzed, and a strong correlation was found between their concentrations and Apelin levels. Considerable elevation of serum nitrogen compounds like urea and creatinine, as well as fasting blood glucose and glycated hemoglobin (HbA1c) were observed  in the type 2 diabetic nephropathy patients. A positive correlation between Apelin and both creatinine and glycated hemoglobin levels was observed. Conversely, a negative correlation was observed between Apelin and the glomerular filtration rate (GFR), indicating potential implications for kidney function in these patients. These findings emphasize the significance of monitoring Apelin concentration along with other biochemical variables as essential indicators for the management and understanding of type 2 diabetic nephropathy. Further research in type 2 diabetic nephropathy  could offer valuable insights into potential interventions and treatment strategies for improving patient outcomes.